Structural and functional properties of modified cellulose ingredients and their application in reduced-fat meat batters. (January 2023) - Bohrer, B.M.; Izadifar, M.; Barbut, S.
Abstract: The first goal for this experiment was to determine the structural and technological characteristics for methylcellulose (MC ), carboxymethyl cellulose (CMC ), and microcrystalline cellulose (MCC ), while the subsequent goal for this experiment was to determine the application of the modified cellulose ingredients in reduced-fat meat batters. Each ingredient was characterized and then evaluated as a fat replacer using meat batters with targeted fat levels of 20%, 10%, and 5%. It was determined that each modified cellulose ingredient was unique in its structural and technological properties which caused significant effects on the physiochemical properties of the meat batters. Specifically, MC created inconsistences during heating and cooling of meat batters resulting in elevated cooking loss but did not change textural hardness of cooked samples, CMC appeared to interfere with the meat batter matrix resulting in lower textural hardness but maintained levels of cooking loss, and MCC had similar levels of cooking loss and textural hardness when compared with the control samples. Highlights: The differences in technological function of modified celluloses were demonstrated. Modified celluloses impact physiochemical properties of meat batters differently. Methylcellulose did not maintain levels of cooking loss in reduced-fat meat batters. Carboxymethyl cellulose appears to interfere with network structure of meat batters. Microcrystalline cellulose may improve texture of reduced fat meat batters.